Health Aspect Study on T-36 House Typology Based on Paola Sassi’s Sustainable Concept and Government Standards - Marvel Yael Funata; Rully Damayanti (Advances in Civil Engineering and Sustainable Architecture, 2025)
Study of T-36 houses (T-36) are increasingly emerging to improving the quality of life of its occupants, especially in terms of nurturing health condition. However, the spatial typology of T-36 houses is often faced with the challenge of utilizing limited spaces that meet basic requirements of physical comfort and health in housing standard. This study aims to analyze the health aspects of T-36 houses based on sustainable building criteria by Paola Sassi and governmental standards. The health aspect comprises three factors of natural lighting, occupant comfort, and harmony with nature. The study uses descriptive qualitative method by analyzing design variation of T-36 houses that are available in the housing market. This analysis of 10 designs of T-36 houses indicated varying compliance with the three factors identified in the study; some houses met the criteria, while others did not.